Zur Kenntnis der parasitischen Hymenopteren von Spilococcus nanae Schmutterer in Oberbayern (Homoptera: Coccoidea; Hymenoptera: Chalcidoidea & Proctotrupoidea). - Bachmaier, Franz (Contributions to Entomology = Beiträge zur Entomologie, 1963)
Apart from records and notes on the biology of the Pseudococcid Spilococcus nanae Schmutt. there is given a quantitative survey of parasites and hyperparasites reared from this host in the national trust property "Schwarzlaichmoor", Ldkr. Schongau (Oberbayern), between 1956 and 1959: Leptomastix brevipennis Ferr., Hungariella spilococci (Ferr.), Leptomastidea bifasciata (Mayr), Allotropa mecrida (Walk.), Signiphorina subaenea (Först.), Marietta picta (Andre). Dealing with the above mentioned species there are discussed morphological features as like as problems of taxonomic and biological importance. Nomenclatural Acts spilococci (Ferrière, 1957) (Hungariella), comb. n. hitherto Tetracnemus spilococci Ferrière, 1957